The causal effects between gut microbiota and hemorrhagic stroke: a bidirectional two-sample Mendelian randomization study - Shen, Yingjie; Liu, Hao; Meng, Xiangyi; Gao, Aili; Liu, Yansong; Ma, Wei; Liang, Hongsheng; Hu, Fulan (Frontiers in Microbiology, 2023)
Background: Recent studies have suggested that the composition of gut microbiota (GM) may change after intracerebral hemorrhage. However, the causal inference of GM and hemorrhagic stroke is unknown. Mendelian Randomization (MR) is an effective research method that removes confounding factors and investigates the causal relationship between exposure and outcome. This study intends to explore the causal relationship between GM and hemorrhagic stroke with the help of MR. Methods: Univariable and multivariable MR analyses were performed using summary statistics of the GM (n=18340) in the MiBioGen consortium versus the FinnGen consortium R9 summary statistics (intracerebral hemorrhage, subarachnoid hemorrhage, and nontraumatic intracranial hemorrhage). Causal associations between gut microbiota and hemorrhagic stroke were analyzed using inverse variance weighted, MR-Egger regression, weighted median, weighted model, simple mode, and MR-PRESSO. Cochran's Q statistic, MR-Egger regression, and leave-one-out analysis were used to test for multiplicity and heterogeneity of instrumental variables. Separate reverse MR analyses were performed for microbiota found to be causally associated with hemorrhagic stroke in the forward MR analysis. Also, multivariate MR analyses were conducted after incorporating common confounders. Results: Based on the results of univariable and multivariate MR analyses, Actinobacteria (phylum) (OR, 0.80; 95%CI, 0.66-0.97; P=0.025) had a protective effect against hemorrhagic stroke, while Rikenellaceae RC9 gut group (genus) (OR, 0.81; 95%CI, 0.67-0.99; P=0.039) had a potential protective effect. Furthermore, Dorea (genus) (OR,1.77; 95%CI, 1.27-2.46; P=0.001), Eisenbergiella (genus) (OR, 1.24; 95%CI, 1.05-1.48; P=0.013) and Lachnospiraceae UCG008 (genus) (OR, 1.28; 95%CI, 1.01-1.62; P=0.041) acted as potential risk factors for hemorrhagic stroke. The abundance of Dorea (genus) (β, 0.05; 95%CI, 0.002~0.101; P=0.041) may increase, and that of Eisenbergiella (genus) (β, -0.072; 95%CI, -0.137~-0.007; P=0.030) decreased after hemorrhagic stroke according to the results of reverse MR analysis. No significant pleiotropy or heterogeneity was detected in any of the MR analyses. Conclusion: There is a significant causal relationship between GM and hemorrhagic stroke. The prevention, monitoring, and treatment of hemorrhagic stroke through GM represent a promising avenue and contribute to a deeper understanding of the mechanisms underlying hemorrhagic stroke.